The Identity Basis of Literacy - Yadav Raj Upahaya, (Interdisciplinary Journal of Management and Social Sciences, 2024)
Samakhyanshastra is the science of analyzing Samakhyan, a new theory of literary and non-literary analysis developed after the advent of anthology analysis, modern linguistics, post-structuralism, and narrative analysis. It encompasses unitary aspects such as the narrator, environment, and participants (characters). Samakhya refers to the sender, presenter, or reader personality prepared by the author, who presents the Samakhyan as the speaker or role-player. In the narrative world, the active addressee is the person or agent managing the Samakhyan coherently, giving it a solid shape. Editors, based on their roles, can be omniscient, neutral, integrative, etc. Samakhitas are categorized as open or closed based on self-presentation and as reliable or unreliable from the perspective of credibility. Narratives are classified as external or internal based on their relationship with the story. The narrator may remain detached or attached, depending on their character affiliation. The study of Samakhyan and Samakhyanshastra, along with the introduction and types of Samakhyan, are explored under sub-headings. Thus, its central focus is the introduction and categorization of journalism.